A l'entorn de l'adquisició de la sintaxi i del seu estudi - Rosselló, Joana; Llinàs, Mireia; Bel, Aurora (Caplletra. Revista Internacional de Filologia, 2003)
This article reflects upon new observations and old concepts related to the acquisition of syntax by examining the strengths and weaknesses of research in acquisitional syntax. Two of the strengths are the interdisciplinary nature of child acquisitional studies and the potential dialogue between research in theoretical syntax and acquisitional syntax. A weakness, possibly the result of excessive specialization, is the lack of real dialogue in general debates related to central foundational concepts in syntax, such as the poverty of stimulus argument or the conception of Universal Grammar. This article reviews two recent publications that touch upon these topics and discusses the results in light of research in early syntax within the generative paradigm.